Use of geological and geomorphological parameters in potential suitability assessment for urban planning development at Wadi Al-Asla basin, Jeddah, Kingdom of Saudi Arabia - Youssef, Ahmed M.; Pradhan, Biswajeet; Sefry, Saleh A.; Abdullah, Mazen M. Abu (Springer Verlag, 2015)
During the planning of urban environment, usually economic and social parameters are taken into consideration. As a result, urban planning areas are susceptible and vulnerable to different types of natural disasters, which cause extensive damages to these areas. In the current study, for the protection of the urban environment, a unique approach of urban planning and sustainable development is proposed. The study area is the Wadi Al-Aska basin (East of Jeddah City), Saudi Arabia. Before the suitability analysis, urban development in the Jeddah area from 1973 to 2009 was applied. In the current study, an integrated evaluation of the suitable areas for urban development is proposed by using geological, geomorphological, and geographical characteristics of the study area as well as flash flood hazard factor. The used parameters were correlated by using the analytical hierarchical process (AHP) method and incorporated into a geographic information system (GIS) in order to produce the corresponding suitability maps. The study area is classified into five categories including very high, high, moderate, low, and very low suitability for urban development. These can be attributed mainly to the fact that in the majority of cases, only geographical, social, and economical factors were used for urban development, whereas in the current study, geomorphological, geographical, geological, and natural hazards parameters were quantified and taken into account.